Anal human papillomavirus prevalence and risk factors among men who have sex with men in Vietnam. (November 2021) - Tuan, Le Anh; Prem, Kiesha; Pham, Quang Duy; Toh, Zheng Quan; Tran, Hau Phuc; Nguyen, Phuc Duy; Mai, Chu Thi Ngoc; Ly, Le Thi Khanh; Cao, Van; Le-Ha, Tam-Duong; Tuan, Nguyen Anh; Jit, Mark; et al.
Highlights: HPV infection in men having sex with men (MSM) was studied in two cities of Vietnam Prevalence of any HPV and HPV16/18 among MSM was 32.3% and 11.0%, respectively High-risk HPV infections in MSM were associated with risky sexual behaviours A targeted HPV vaccination strategy would be beneficial for MSM in Vietnam Abstract: Objectives: Men who have sex with men (MSM) are at risk of human papillomavirus (HPV)-related cancers, while published data are scarce. This study determined HPV prevalence and risk factors in MSM in Vietnam to inform HPV prevention strategies in this key population. Methods: A cross-sectional study of 799 MSM aged 16-50 years was conducted in Vietnam in 2017-2018. Information was collected on risk behaviours, and knowledge of HPV and anal cancer; rectal swabs were taken to detect anal HPV infection. An in-house polymerase chain reaction and Genoflow HPV array test kit were used for HPV detection and genotyping. Results: The median age of the study participants was 25 years (range 18-52). Overall prevalence of any HPV and HPV16/18 infection was 32.3% and 11.0%, respectively. A higher prevalence of high-risk HPV infection to all 14 types tested was found in Ho Chi Minh City (30.9%) than in Hanoi (18.4%). High-risk HPV infection was associated with inconsistent condom use and history of engaging in sex under the influence of drugs (adjusted odds ratio (aOR), 2.27; 95% CI, 1.48-10.67), as well as having multiple sexual partners (aOR, 1.01; 95% CI, 1.00–1.02). Conclusions: High-risk anal HPV infections in Vietnamese MSM were significantly associated with risky sexual behaviours. A targeted HPV vaccination strategy would have substantial benefit for MSM in Vietnam.